The Effect Of Brand Image On The Purchase Decision Stages Of The Amplang Sari Belidak Product in Ketapang City - Dewi Kurniati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Increasing competition in the food and beverage sector requires SMEs to build a strong brand image in order to attract and retain customers. Amplang Sari Belidak, a traditional snack from KetapangCity, has market potential but still faces challenges in expanding its market reach. This study employs a quantitative descriptive method with purposive sampling, the respondents consist of 100 consumers who have purchased Amplang Sari Belidak at least once in the past six months. Data were collected via a questionnaire using a Likert scale and analyzed using Structural Equation Modeling – Partial Least Square (SEM-PLS) with the assistance of SmartPls 4.0. software. The results indicate that brand image has a positive and significant influence on the stages of the purchase decision process, with a T-Statistic value of 3.151 and a P-Value of 0.000. An R-Square value of 0.838 indicates that brand image explains 83.8% of the variation in the purchase decision stages, and a Q-Square value of 0.525 indicates that the model has good predictive relevance. The most dominant indicators in shaping brand image are corporate image, particularly consumer trust in the manufacturer and corporate reputation. These findings suggest that a strong brand image can drive consumer purchasing decisions from the need recognition stage through to post–purchase behavior.